Video-Based Learning Media: Pencak Silat Material, Structured Hands-On Practice Method - Tommy Arisman Bate’e; Abdul Hasan Saragih; R. Mursid (RIRAI Publisher, 2024)
This research aims to determine the feasibility of learning media by lining up physical education videos with pencak silat material and to determine the effectiveness of learning media by lining up physical education videos with pencak silat material on student learning outcomes. The stages of this research are the needs analysis stage, the learning media planning stage lined up with pencak silat material videos (design), the development stage (develop), and the testing stage (validation). The results of this study show that (1) the learning outcomes of the minimum pretest score for the control group were 41 and the highest score was 70, while the average score was 54.92%. (2) The learning outcomes of the minimum posttest score for the control group were 41, and the highest score was 80, while the average score was 62.58%. (3) The distribution of pretest learning results with a score of 41–48 is in the strongly disagree category; there is 1 student with a percentage (8.3%) the same as the posttest. (4) The distribution of pretest learning results with a score of 49–56 was in the disagree category; there was 1 student with the same percentage (8.3%) as the posttest. (5) The distribution of pretest learning outcomes with a score of 57–64 was in the neutral category; there were 5 students with a percentage (41.7%) and posttest 4 students with a percentage (33.3%). (6) The distribution of pretest learning results with a score of 65–72 is in the neutral category; there are 3 students with a percentage (25.0%) the same as the posttest. (7) The distribution of pretest learning results with a score of 73–80 is neutral; there were 2 students with a percentage of 16.7% and 3 students with a percentage of 25.0%). The results of hypothesis testing using the independent sample T-test by looking at the probability sig. (2-tailed) show a coefficient of 0.103. greater than 0.05, it can be concluded that there is a difference.